2010
DOI: 10.1002/gps.2412
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Dutch homes for the elderly: under‐diagnosis in demented residents?

Abstract: The prevalence of diagnosed depressive disorders was comparable between demented and non-demented residents. However, demented residents suffered more from mood symptoms and may be at risk of under-diagnosis of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Within the group of residents with depressive symptoms, residents with and without dementia did not differ significantly with regard to the prevalence rates of depressive disorders. Baller et al () found that among residents in homes for the aged with depressive symptoms according to the MDS‐DRS, those with dementia were significantly less likely to be diagnosed with a depressive disorder than residents without dementia. They concluded that residents with dementia in homes for the aged were at an increased risk for under‐diagnosis of depression as compared with those without dementia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the group of residents with depressive symptoms, residents with and without dementia did not differ significantly with regard to the prevalence rates of depressive disorders. Baller et al () found that among residents in homes for the aged with depressive symptoms according to the MDS‐DRS, those with dementia were significantly less likely to be diagnosed with a depressive disorder than residents without dementia. They concluded that residents with dementia in homes for the aged were at an increased risk for under‐diagnosis of depression as compared with those without dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, knowledge on diagnosis and treatment in daily nursing home practice is important, focused on both types of residents. Only a few studies have been carried out focusing simultaneously on both groups in nursing homes or homes for the aged (Janzing et al , ; Davison et al , ; Baller et al , ). A recent Dutch study in homes for the aged suggests that residents with dementia are more at risk of being under‐diagnosed for depression than residents without dementia (Baller et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…8 Prevalence rates of 30% to 50% have been reported for depression in dementia at all stages of cognitive decline. 9 In contrast to agitation, depression often remains unrecognized 10 because it presents differently compared with younger patients not suffering from dementia 11 and because patients with more severe cognitive impairment are sometimes unable to express distress adequately. 9 Untreated depressive symptoms accelerate the course of the disease in dementia, 12 and depression is associated with mortality in the elderly.…”
mentioning
confidence: 99%
“…Recent prevalence estimates suggest that clinically significant depressive symptoms or depressive disorders affect 20% to more than 50% of LTC residents with dementia (Baller et al, 2010; Jongenelis et al, 2004; Payne et al, 2002; Teresi, Abrams, Holmes, Ramirez, & Eimicke, 2001; Zubenko et al, 2003). This is important in LTC settings, where Alzheimer’s disease or other dementia affects an estimated 47% to 67% of residents (Alzheimer’s Association, 2011).…”
mentioning
confidence: 99%
“…Despite the evident prevalence of depression in LTC settings, symptoms of depression often go undetected and undiagnosed, particularly in residents with dementia (Baller et al, 2010; Davidson, Koritsas, O’Connor, & Clarke, 2006). First, consensus on the most valid method to assess and diagnose depression in dementia is lacking; thus, diagnostic criteria differ among experts (Starkstein, Mizrahi, & Power, 2008).…”
mentioning
confidence: 99%